The Role of Mitochondria-Associated Reactive Oxygen Species in the Amyloid β Induced Production of Angiogenic Factors b y ARPE-19 Cells - Wu, L.; Tan, X.; Liang, L.; Yu, H.; Wang, C.; Zhang, D.; Kijlstra, A.; Yang, P. (Current Molecular Medicine, 2017)
Objective: This study aimed to investigate the mechanisms whereby Amyloidbeta (Aβ) induces the production of angiogenic factors by a human retinal pigment epithelial cell line (ARPE-19) cells. Methods: ARPE-19 cells obtained from the American Type Culture Collection (ATCC) were utilized in this study. The expression level of vascular endothelial growth factor (VEGF), Interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1) and complement activation fragments C3a and C5a were measured by Real-time quantitative PCR (RT-PCR) and Enzyme-linked immunosorbent assay (ELISA). The production of mitochondria-associated reactive oxygen species (ROS) was measured by flow cytometry. Results: The expression of VEGF, IL-8, MCP-1, C3a and C5a was significantly increased in Aβ-treated ARPE-19 cells. Mitochondria-associated ROS production was also significantly increased when exposed to Aβ. Inhibition of mitochondrial ROS with Diphenyleneiodonium chloride (DPI) markedly decreased the Aβ induced production of VEGF, IL-8, MCP-1, C3a and C5a by ARPE-19 cells. Anti-C3a or anti-C5a neutralizing antibodies did not have a detectable influence on the secretion of VEGF, IL-8 and MCP-1 by ARPE-19 cells upon stimulation with Aβ. Conclusion: Our results support the hypothesis that Aβ is involved in the pathogenesis of choroidal neovascularization (CNV) formation by promoting the production of the angiogenic cytokines VEGF, IL-8 and MCP-1 by RPE cells. Mitochondrial ROS was shown to play a role in the regulation of Aβ induced expression of these cytokines.
Keywords: retinal pigment epithelium